172 Quality improvement project on the peri-procedural management of lumbar punctures. Issue 6 (27th May 2022) - Mousele, Christina; Gillingham, Alexandra; Mummery, Catherine; Carr, Aisling
Abstract : Introduction: Cancellation rate of elective lumbar punctures (LPs) due to inappropriate management of antithrombotic medications and lack of adequate training of junior doctors in the peri-procedural man- agement of LPs encouraged us to conduct a quality improvement project aiming to address these issues. Methods: Retrospective review of day case elective LPs (01/10/2018 - 01/01/2019) Junior doctor surveys aiming to assess LP related knowledge and confidence Results: 37.5% (75/200) of the scheduled LPs were cancelled due to mistakes in the pre-procedural man- agement of patients' blood-thinning medication. Junior doctors' knowledge of consent and antithrom- botic management was suboptimal. As was self-reported confidence and competency in independent performance of LPs at CMT/SHO level. Change implemented: Implementation of Trust-approved Guidelines on peri-procedural management of LPs based on systematic review of literature LP training clinic Re-audit.LP cancellation rate fell to 8% after implementation of these measures (15/04/2019 - 15/07/2019) with meaningful improvement in LP knowledge/confidence of junior doctors. christinamousele92@gmail.com